Event-triggered Control Strategies for Rendezvous Problem of Multiple Linear Systems - Dong, Yi (IEEE International Conference on Control and Automation (Print), 2020)
This paper studies the rendezvous problem of linear multi-agent systems by event-triggered strategies based on piecewise constant communication signals of neighboring agents. There are two distinguished features of the design. First, the distributed event-triggered control laws can not only accomplish tasks of asymptotic tracking and external disturbance rejection as existing event-triggered consensus control strategies, but also have the additional ability of maintaining the connectivity of the time-varying and position-dependent communication network as existing rendezvous controllers. Second, by combining potential function technique, output regulation theory and adaptive control technique, an event-triggered observer is applied to estimate both the leader's system matrix and signal, which can work in parallel with the distributed event-triggered control, i.e., the executive time instants for the observer and the control are asynchronous and generated by different triggering functions based on their own locally available measurement errors.